2009
DOI: 10.1007/s11628-009-0068-4
|View full text |Cite
|
Sign up to set email alerts
|

Airline customer satisfaction and loyalty: impact of in-flight service quality

Abstract: Service quality, Customer satisfaction, Customer loyalty, Airline companies, In-flight service,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(106 citation statements)
references
References 25 publications
5
78
0
7
Order By: Relevance
“…In airline operations, the body of evidence indicates that service quality perceptions, as well as satisfaction obtained through service encounters are essential to enhancing customer loyalty [An, Noh, 2009]. Literally, loyalty denotes customer propensities towards the service company and its product/service.…”
Section: Background To the Studymentioning
confidence: 99%
“…In airline operations, the body of evidence indicates that service quality perceptions, as well as satisfaction obtained through service encounters are essential to enhancing customer loyalty [An, Noh, 2009]. Literally, loyalty denotes customer propensities towards the service company and its product/service.…”
Section: Background To the Studymentioning
confidence: 99%
“…Many studies have investigated the effects of SQ on consumer behaviors, such as CS, customer loyalty, and behavioral intentions, as well as on firm performance, in various service industries [14,[37][38][39] and found it to have a positive impact [37,40]. Lee and Cunningham [37] indicated that service quality perceptions have a positive impact on service loyalty in banks and travel agencies, while Santos [12] found that high E-service quality provides long-term benefits to companies in the E-commerce industry.…”
Section: Service Qualitymentioning
confidence: 99%
“…With regard to airline services in particular, previous studies have aimed to identify the determinants of BI [14,15]. As it is among the most critical success factors related to the profitability and performance of airline service firms, many studies have focused on the influence of service quality (SQ) on BI [16]; however, CSR initiatives are still not regarded as important factors of business success in the airline industry.…”
Section: Introductionmentioning
confidence: 99%
“…The moderating effects of gender and education have also been tested in models of online consumer behaviour (Sánchez et al 2009;Richard et al 2010). In the context of airline companies it has been demonstrated that satisfaction (An and Noh 2009;Hau and Thuy 2011), trust and perceived value are the antecedents of loyalty in the offline environment (Forgas et al 2010); however, there have been no studies identifying these antecedents of loyalty to websites or the moderating effects of the gender and education of the users of airline companies' websites. Identifying the antecedents of e-loyalty to airline companies is especially important bearing in mind that 25.8% of sales are being made directly through their websites and for 2013 is expected to increase to 38% .…”
Section: Introductionmentioning
confidence: 99%